Orlando a biography - Woolf, Virginia, 1882-1941. (New York, Harcourt Brace Jovanovich, 1973)
Orlando doubles as first an Elizabethan nobleman and then as a Victorian heroine who undergoes all the transitions of history in this novel that examines sex roles and social mores.
Keywords: Transsexuals -- Fiction; Nobility -- Fiction; Sex role -- Fiction; England -- Fiction; Historical fiction; Fantasy fiction